1998
DOI: 10.1002/(sici)1521-4141(199810)28:10<2991::aid-immu2991>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Transient alteration of T cell fine specificity by a strong primary stimulus correlates with T cell receptor down-regulation

Abstract: P14 mice expressing a transgenic TCR specific for the lymphocytic choriomeningitis virus glycoprotein p33 epitope were used to study the induction of CTL effector activity by a variety of ligands. Surprisingly, p33 variants which are weaker agonists for the P14 TCR than the wild-type p33 peptide were able to induce more potent effectors with a broader range of cytolytic specificity. Similarly, low concentrations of p33 were more effective than higher concentrations. These results correlated with no or only mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…We observed a greater loss of CD3 expression when anti-CD3 stimulation was augmented by cocross-linking CD28 or adding monocytic APC, suggesting that the extent of CD3 down-regulation may be regulated by signal strength as shown in studies of TCR down-regulation in T-cell clones treated with peptide agonists and antagonists. 44 Because it is difficult to isolate antigen-specific effector T cells without defined major histocompatibility complex (MHC) class II-tetramer reagents, we are currently examining whether CD3 loss occurs in human effector CD4 T cells generated by alloantigen stimulation. There are at least 3 possibilities to account for the apparent loss of CD3 expression in effector T cells; first, CD3 may partition to another portion of the cell; second, CD3 may be degraded, and finally, CD3 may be continuously and rapidly recycled through the endocytic compartment.…”
Section: Discussionsupporting
confidence: 74%
“…We observed a greater loss of CD3 expression when anti-CD3 stimulation was augmented by cocross-linking CD28 or adding monocytic APC, suggesting that the extent of CD3 down-regulation may be regulated by signal strength as shown in studies of TCR down-regulation in T-cell clones treated with peptide agonists and antagonists. 44 Because it is difficult to isolate antigen-specific effector T cells without defined major histocompatibility complex (MHC) class II-tetramer reagents, we are currently examining whether CD3 loss occurs in human effector CD4 T cells generated by alloantigen stimulation. There are at least 3 possibilities to account for the apparent loss of CD3 expression in effector T cells; first, CD3 may partition to another portion of the cell; second, CD3 may be degraded, and finally, CD3 may be continuously and rapidly recycled through the endocytic compartment.…”
Section: Discussionsupporting
confidence: 74%
“…The Nature and Dose of the Ligand Determines the Sensitivity of Antibody-induced TCR Down-modulation to PTK Inhibitors-Conflicting results have been obtained from different studies on the PTK dependence of antibody-induced TCR downmodulation (15)(16)(17)(18)(19). One reason for such variation could be the use of soluble or immobilized (plate-bound) antibodies.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies suggest that the TCR internalization and down-modulation are protein-tyrosine kinase (PTK)-dependent processes that ultimately result in the degradation of the TCR (5,(15)(16)(17). However, in other studies PTK inhibitors did not affect TCR downmodulation (18,19).…”
Section: Regulation Of Tcrmentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrate here that stimulation of memory CD4 T cells with a strong avidity peptide induces the highest level of apoptosis compared with stimulation with the native or weak avidity peptide, consistent with reports showing that a strong agonist can trigger death of activated T cells (45). Moreover, we found that high avidity stimulation led to extensive TCR down-regulation that likely results in reduced Ag responsiveness, as has been previously demonstrated for CTL clones (46). Conversely, low avidity stimulation is associated with a high association/dissociation kinetics (47) that may account for the maintenance of TCR expression in L115-boosted memory T cells.…”
Section: Discussionmentioning
confidence: 99%